An Oxygenophilic Atomic Dispersed FeNC Catalyst for Lean‐Oxygen Seawater Batteries. Issue 23 (30th April 2021) - Meng, Rongwei; Zhang, Chen; Lu, Ziyang; Xie, Xiaoying; Liu, Yingxin; Tang, Quanjun; Li, Huan; Kong, Debin; Geng, Chuan‐Nan; Jiao, Yan; Fan, Zehui; He, Qing; et al.
Abstract: A constant energy supply is crucial for the exploration of deep‐sea extreme environments, and a self‐powered energy conversion device is ideal for this situation. Dissolved‐oxygen seawater batteries (SWBs) that generate electricity by reducing the dissolved oxygen are promising candidates but the ultralow oxygen concentration in deep sea limits the reaction kinetics. As a result, oxygenophilic electrocatalysts for lean‐oxygen conditions are urgently needed. A microwave heating method is reported that achieves the ultrafast synthesis of atomic dispersed FeNC catalyst (FeNgraphene (G)/carbon nanotube (CNT)), which possesses high activity and strong oxygenophilic interface between graphene and CNTs. DFT calculations and experimental results both show that the high oxygenophilicity is due to the double‐adsorption sites on the G/CNT interface, and the high activity FeN4 active sites is caused by the charge separation. FeNG/CNT catalysts have an outstanding oxygen reduction reaction (ORR) performance in both O2 ‐saturated alkaline medium and neutral seawater with half‐wave potentials ( E 1/2 ) of 0.929 and 0.704 V, respectively, far better than commercial Pt/C. A SWB shows excellent performance in lean‐oxygen seawater (≈0.4 mg L −1 ), with a discharge voltage of 1.18 V at 10 mA cm −2 . These results suggest a critical role for oxygenophilic catalyst specifically for SWBs under lean‐oxygen conditions. Abstract : Seawater batteries (SWBs) that convert chemical energy into electricity are highly desirable for underwater exploration. Oxygenophilic atomic dispersed electrocatalysts (FeNgraphene (G)/carbon nanotube (CNT)) are proposed to realize the enhanced oxygen reduction reaction (ORR) kinetics for lean‐oxygen SWBs. The FeNG/CNT shows superior ORR performance compared with Pt/C and the resulting SWBs can operate stably in lean‐oxygen seawater (≈0.4 mg L −1 ) even at low temperatures.